Physiological roles of the chloroplast acetyltransferase GNAT1 and GNAT2 in Arabidopsis thaliana - Ami, Shahnawaz (My University, 2024)
The acetylation machinery in the chloroplast consists of eight acetyltransferase enzymes that belong to the General control non-repressible 5-related N-acetyltransferase (GNAT) superfamily. Loss of the GNAT2 enzyme has been shown to affect regulation of photosynthetic light harvesting, thylakoid dynamics, plant phenotype and acetylation level of chloroplast proteins, but the detailed effects on seed germination, root development, thylakoid protein acetylation and de novo synthesis of Photosystem II (PSII), are yet to be studied. Therefore, the aims of my thesis are (i) to understand the effect of GNAT2 on thylakoid protein accumulation and acetylation of light-harvesting complex II (LHCII) proteins; (ii) to assess the germination and root morphology of wild-type (WT) and gnat2 knock-out mutant under standard conditions and osmotic stress; (iii) to understand the role of GNAT1 and GNAT1/2 in the early stages of PSII biosynthesis in Arabidopsis thaliana. For the analysis of GNAT2’s effect on thylakoid protein accumulation, proteins extracted from five weeks old WT and gnat2 plants were separated by 2D sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and analysed by liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS). For the assessment of germination and root morphology, WT and gnat2 plants were grown on ½ Murashige Skooog (MS) media under standard and osmotic stress condition induced by 200 mM mannitol. For assessing GNAT1 & GNAT2’s role in PSII biosynthesis, proteins extracted from two weeks old WT, gnat1 and gnat2 plants were subjected to clear native polyacrylamide gel electrophoresis (CN-PAGE). The results obtained indicate that the loss of GNAT2 led to decreased seed germination and overall decrease in root growth under both conditions. Separation of thylakoid proteins by 2D SDS-PAGE followed by LC-MS/MS analysis of revealed that the acetylation level of LHCB 1 and LHCB 2 were clearly decreased in the gnat2 mutant. The analysis of PSII assembly indicated differences in the accumulation of PSII-LHCII supercomplexes and LHCII assembly complex. Overall, the study has potential to bring in new insights into the physiological role(s) of chloroplast protein acetylation.
Keywords: acetylation, acetyltransferase, Arabidopsis, chloroplast, light harvesting protein, Photosystem II, root morphology